Climate Responsive Innovation within the Agricultural Curriculum and Learning System - Wilma van Staden (Environmental Association of Southern Africa, 2020)
The purpose of this paper is to outline the climate responsive innovation process within the agricultural innovation system of the North West Province, South Africa. The focus was on the embedded curriculum and learning activity system and its responses to social-ecological and earth system changes influenced by climate change. It outlines the barriers and processes hampering curriculum and learning innovations towards climate-smart responsiveness, and also examines the processes required to initiate micro and macro innovations. This paper focusses on how actors within the system can initiate curriculum innovation and climate responsiveness through micro innovations when supported and how this can lead to macro innovations. The system experienced various barriers during the innovation process and overcame many challenges during the journey towards climate-smart responsiveness through the identification of contradictions within the system, developing tools to assist in the transitioning process and expansion in the social-spatial dimension by establishing a learning network within the surrounding communities. The research indicated that the catalysing of the curriculum and learning system required specific tools, time and the understanding of the importance of micro-level innovation.